(untitled) (Research, Society and Development, 2024)
Introduction: The intake of omega 3 during pregnancy has been observed for a long time through studies, which indicated that it has several benefits, and it is important to consume it in adequate amounts to avoid certain complications. Objective: to identify the main effects of Omega 3 during pregnancy. Methodology: Through an integrative review, with the aim of finding current scientific content on the subject. For the following review, the following databases were used: Scholar, Virtual Health Library, PubMed and Scielo, published from 2019 to 2024. Results: after the searches, 115 articles were found, however, only 24 articles were used for this research. Conclusion: The use of Omega 3 during pregnancy brings many benefits to both the mother and the baby, developing neurological and visual function of the baby and reducing the chance of premature birth, so Omega 3 supplementation is extremely important during pregnancy.